PENGARUH MODEL PEMBELAJARAN DAN GAYA BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS: (Studi Eksperimen Siswa Kelas V Pada Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar Negeri Bulurokeng Kota Makassar) - Asran; Nadiroh; Etin Solihatin (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This study aims to determine the effect of learning models and learning styles on the critical thinking skills of fifth-grade students of an elementary school in Social Sciences. This experimental study uses Factorial 2x2. Determination of the sample using the Multistage Random Sampling technique, namely class V students of SD Negeri Bulurokeng Makassar. Data analysis used two-way variance analysis and followed by the Tukey test for the significance level α = 0, 05. Test the normality of the data using the Lilliefors test and homogeneity test using the Bartlett test. The results of this study indicate: 1) Critical thinking ability given the Student Team Achievement Division learning model is higher than those given Teams Games Tournament learning model, 2) Critical thinking ability of students with auditory learning styles is higher than students of visual learning styles, 3) There the influence of interaction between learning models and learning styles on students' critical thinking abilities, 4) The ability to think critically with auditory learning styles given the Student Team Achievement Division learning model is higher than the Teams Games Tournament model, 5) Ability to think critically with visual learning styles given Student Team Achievement Division model is lower than students given Teams Games Tournament learning model, 6) Critical thinking ability of auditory learning style students who are given the Student Team Achievement Division model is higher than visual learning style students with Teams Games Tour model Namely, and 7) Critical thinking ability of auditory learning style students were given a lower Teams Games Tournament model than visual learning style students with the Teams Games Tournament model. The novelty of this research is in terms of age, namely at the elementary school level. While the two previous studies were conducted at high school age. Furthermore, this study used the Student Teams Achievement Division and Teams Games Tournament models while previous research conducted by Anit Pranita Devi used Think Pair Share and Jigsaw learning models. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran dan gaya belajar terhadap kemampuan berpikir kritis siswa kelas V sekolah dasar pada Ilmu Pengetahuan Sosial. Penelitian eksperimen ini menggunakan Factorial 2x2. Penentuan sampel menggunakan teknik Multistage Random Sampling yaitu siswa kelas V SD Negeri Bulurokeng Makassar. Analisis data menggunakan analisis varian dua cara dan diikuti dengan uji Tukey untuk tingkat signifikansi α = 0, 05. Uji normalitas data menggunakan uji Lilliefors dan uji homogenitas menggunakan uji Bartlett. Hasil penelitian ini menunjukkan: 1) Kemampuan berpikir kritis yang diberi model pembelajaran Student Team Achievement Division lebih tinggi dibandingkan yang diberi model pembelajaran Teams Games Tournament, 2) Kemampuan berpikir kritis siswa dengan gaya belajar auditori lebih tinggi dibandingkan siswa gaya belajar visual, 3) Terdapat pengaruh interaksi antara model pembelajaran dan gaya belajar terhadap kemampuan berpikir kritis siswa, 4) Kemampuan berpikir kritis dengan gaya belajar auditori yang diberi model pembelajaran Student Team Achievement Division lebih tinggi dibanding model Teams Games Tournament, 5) Kemampuan berpikir kritis dengan gaya belajar visual yang diberi model Student Team Achievement Division lebih rendah dibandingkan siswa yang diberi model pembelajaran Teams Games Tournament, 6) Kemampuan berpikir kritis siswa gaya belajar auditori yang diberi model Student Team Achievement Division lebih tinggi dibanding siswa gaya belajar visual dengan model Teams Games Tournament, dan 7) Kemampuan berpikir kritis siswa gaya belajar auditori diberi model Teams Games Tournament lebih rendah dibanding siswa gaya belajar visual dengan model Teams Games Tournament. Kebaruan penelitan ini adalah dari segi usia yakni pada jenjang sekolah dasar. Sedangkan kedua penelitian sebelumnya dilakukan pada usia sekolah menengah atas. Selanjutnya, penelitian ini menggunakan model Student Teams Achievement Division dan Teams Games Tournament sementara penelitian sebelumnya yang dilakukan Anit Pranita Devi menggunakan model pembelajaran Think Pair Share dan Jigsaw. Kata Kunci: Student Team Achievement Division, Teams Games Tournament, Gaya Belajar, Kemampuan Berpikir Kritis